![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)2x( 2x-1) -(2x-1)
=(2x-1)(2x-1)
=(2x-1)2
b)2x( 4x + 2x + 1) - ( 4x + 2x +1)
=(2x-1)(4x+2x+1)
=(2x-1)(6x+1)
a) \(2x\left(2x-1\right)-\left(2x-1\right)=\left(2x-1\right)\left(2x-1\right)\)
b) \(2x\left(4x+2x+4\right)-\left(4x+2x+4\right)=\left(2x-1\right)\left(4x+2x+4\right)\)
Mik làm cho vui thôi chứ chẳng ai T mik đâu
![](https://rs.olm.vn/images/avt/0.png?1311)
* Trả lời:
\(\left(1\right)\) \(-3\left(1-2x\right)-4\left(1+3x\right)=-5x+5\)
\(\Leftrightarrow-3+6x-4-12x=-5x+5\)
\(\Leftrightarrow6x-12x+5x=3+4+5\)
\(\Leftrightarrow x=12\)
\(\left(2\right)\) \(3\left(2x-5\right)-6\left(1-4x\right)=-3x+7\)
\(\Leftrightarrow6x-15-6+24x=-3x+7\)
\(\Leftrightarrow6x+24x+3x=15+6+7\)
\(\Leftrightarrow33x=28\)
\(\Leftrightarrow x=\dfrac{28}{33}\)
\(\left(3\right)\) \(\left(1-3x\right)-2\left(3x-6\right)=-4x-5\)
\(\Leftrightarrow1-3x-6x+12=-4x-5\)
\(\Leftrightarrow-3x-6x+4x=-1-12-5\)
\(\Leftrightarrow-5x=-18\)
\(\Leftrightarrow x=\dfrac{18}{5}\)
\(\left(4\right)\) \(x\left(4x-3\right)-2x\left(2x-1\right)=5x-7\)
\(\Leftrightarrow4x^2-3x-4x^2+2x=5x-7\)
\(\Leftrightarrow-x-5x=-7\)
\(\Leftrightarrow-6x=-7\)
\(\Leftrightarrow x=\dfrac{7}{6}\)
\(\left(5\right)\) \(3x\left(2x-1\right)-6x\left(x+2\right)=-3x+4\)
\(\Leftrightarrow6x^2-3x-6x^2-12x=-3x+4\)
\(\Leftrightarrow-15x+3x=4\)
\(\Leftrightarrow-12x=4\)
\(\Leftrightarrow x=-\dfrac{1}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a,(5x-1)6=36
5x-1=3
x=4/5
b,(2x+1)3=0,13
2x+1=0,1
x=-0,45
c,(2x-3)4=(2x-3)4(2x-3)2
(2x-3)2=0
2x-3=0
x=3/2
d,(2x+1)5=(2x+1)5(2x+1)2005
(2x+1)2005=0
2x+1=0
x=-1/2
Bài làm:
Ta có: \(\left(2x-1\right)^3=\left(2x-1\right)^4\)
\(\Leftrightarrow\left(2x-1\right)^4-\left(2x-1\right)^3=0\)
\(\Leftrightarrow\left(2x-1\right)^3\left(2x-1-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}\left(2x-1\right)^3=0\\2x-2=0\end{cases}\Leftrightarrow}\orbr{\begin{cases}2x=1\\2x=2\end{cases}\Rightarrow}\orbr{\begin{cases}x=\frac{1}{2}\\x=1\end{cases}}\)
Trả lời:
\(\left(2x-1\right)^3=\left(2x-1\right)^4\)
\(\Leftrightarrow1=2x-1\)
\(\Leftrightarrow2x=2\)
\(\Leftrightarrow x=1\)
Vậy \(x=1\)